1994
DOI: 10.1161/01.hyp.23.6.1091
|View full text |Cite
|
Sign up to set email alerts
|

Increased barium influx and potassium current in stroke-prone spontaneously hypertensive rats.

Abstract: Arterial potassium permeability is increased in hypertension. In this study we conducted voltage-clamp experiments to determine whether the whole-cell K + current is increased in a Ca 2+ -dependent manner in aortic smooth muscle cells from stroke-prone spontaneously hypertensive rats (SHRSP

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Subsequent studies using the patch clamp technique provided additional evidence regarding increased BK channel function in VSMCs during hypertension. In agreement with vessel reactivity studies, results published from several laboratories indicate that compared to control, whole cell K + current through iberiotoxin-sensitive BK channels is elevated in VSMCs from aorta of SHR, stroke-prone SHR, and rats with renal hypertension [150,151,153,154,161]. Additionally, myocytes from mesenteric arteries of DOCA salt-induced hypertensive rats also exhibited elevated iberiotoxin-sensitive K + current compared to myocytes from Sham animals [165].…”
Section: Vascular Ion Channel Remodeling During Hypertensionsupporting
confidence: 70%
“…Subsequent studies using the patch clamp technique provided additional evidence regarding increased BK channel function in VSMCs during hypertension. In agreement with vessel reactivity studies, results published from several laboratories indicate that compared to control, whole cell K + current through iberiotoxin-sensitive BK channels is elevated in VSMCs from aorta of SHR, stroke-prone SHR, and rats with renal hypertension [150,151,153,154,161]. Additionally, myocytes from mesenteric arteries of DOCA salt-induced hypertensive rats also exhibited elevated iberiotoxin-sensitive K + current compared to myocytes from Sham animals [165].…”
Section: Vascular Ion Channel Remodeling During Hypertensionsupporting
confidence: 70%
“…Electrophysiological studies have reported increased (282, 286), decreased (170, 171, 279, 288, 886, 947, 1414), or no change (887, 890) in K V current density. One possible explanation for these differences relates to the experimental conditions used to study K V currents; examination of studies on SMCs from the same vessel, recorded in the same lab are particularly illuminating (282, 288).…”
Section: Kv Channelsmentioning
confidence: 99%
“…6 The majority of studies show that the functional expression of BK Ca channels in VSMCs increases during hypertension. [7][8][9][10][11][12][13][14][15] This important local protective mechanism keeps cerebral blood flow at normal or near-normal levels during chronic hypertension. 16,17 In cerebral artery smooth muscle cells (CASMCs), spontaneous and local increases of intracellular Ca 2+ because of the opening of ryanodine receptors (RyRs) in the sarcoplasmic reticulum (SR), visualized as Ca 2+ sparks, activate BK Ca channels on the sarcolemma and so generate spontaneous transient outward currents (STOCs).…”
mentioning
confidence: 99%